Laporan Kasus Pemberian Tindakan Keperawatan dengan Massage Payudara pada Ibu Post Partum Primipara - Fatima, Nur; Ani, Yusni Juwita; Muhsinah, Sitti (PT Karya Inovasi Berkelanjutan, 2025)
Postpartum is the period following childbirth during which a mother adjusts to physiological and psychological changes. Breastfeeding problems caused by breast conditions are common in the early postpartum weeks. These issues require proper follow-up to help mothers navigate the puerperal period successfully and support optimal exclusive breastfeeding. Postnatal breast care aims to enhance breast milk production by stimulating the mammary glands through massage. This case report presents nursing care provided to Mrs. W (24 years old, G1 P0 A0), whose main complaint was insufficient milk production. The nursing care plan included breast massage and breastfeeding education. The procedures followed were based on standard operational protocols. Nursing interventions were administered over a period of three days. On the first day, the total breastfeeding observation score was 2, with the following indicators: engorged breasts due to milk accumulation (0), good let-down reflex (0), breastfeeding frequency > 8 times/day (0), alternating use of both breasts (0), proper latching position (0), on-demand feeding (0), and expression of milk due to fullness (0). On the second day, the total observation score improved to 9, although the mother was still seen expressing milk due to breast fullness (0). By the third day, the observation score reached 10, with all criteria met. In conclusion, the implementation of breast massage resulted in improved breastfeeding status, increasing the score from 2 on the first day to 10 on the third day. In addition to breast massage, the mother received health education on the benefits and techniques of breast massage for independent practice. These results support the use of breast massage as a nursing intervention for primiparous postpartum mothers.